Comparison of prone-supine versus supine position for the treatment of pilon fractures via modified posteromedial approach combined with anterolateral approach. Issue 1 (January 2023) - Guo, Changjun; Zhu, Yuan; Li, Chunguang; Li, Xingchen; Yang, Chonglin; Xu, Xiangyang
Abstract: Background: Most of modified posteromedial approaches require prone position for the treatment of pilon fractures. We describe the technique of modified posteromedial approach under supine position. The goal of the study was to compare the radiographic and clinical outcomes of prone-supine versus supine position for the treatment of pilon fractures via modified posteromedial approach combined with anterolateral approach. Methods: A total of 50 retrospectively consecutive pilon fractures that underwent open reduction internal fixation via modified posteromedial approach combined with anterolateral approach from 2016 to 2019 were reviewed at least a two-year follow up. The positions of patients were divided into two groups: prone-supine versus supine position (26 vs 24, respectively). The operation time, radiographic outcomes including bone union time and ratio of congruent articular reduction were evaluated. The post-operative function was evaluated using the Manchester Oxford score (MOXFQ) and the visual analogue score (VAS). The motion of ankle joint and complications and were also compared. Results: The mean follow-up was 42.2(24.7–73.0) months in the prone-supine group and 42.7(37.3–56.5) months in the supine group (P = .87). The mean operation time was 141.9 ± 10.1 min in the prone-supine group and 107.5 ± 18.9 min in the supine group (P = .00). There was no significant difference in the bone union time and ratio of congruent articular reduction between the two groups. There was no significant difference in the final MOXFQ score, VAS score, and the mean range of ankle motion between the two groups (P > .05). The total incidence of complications was 11.5% in the prone-supine group and 16.6% in the supine group (P = .66). Conclusion: The patient in the prone-supine position versus supine position for pilon fractures via modified posteromedial approach combined with anterolateral approach contributed comparable quality of reduction, bone union time functional outcomes and complications. The supine technique was significantly shorter in terms of operation time.